Towards the improvement of productivity and irrigation efficiency of olive hedgerows managed with mechanical pruning and harvest under various deficit irrigation strategies in Argentina - Calvo, Franco Emmanuel; Calahorra, Maria Andrea; Trentacoste, Eduardo Rafael (Taylor and Francis, 2025)
One of the main challenges in super high-density olive is maintaining hedgerow structure suitable for mechanical harvesting. Deficit irrigation strategies (DI) can contribute to this maintenance. In this study, three DI treatments at 50% of the Control (DI-1: budbreak to pre-bloom, DI-2: fruit set to pit hardening, and DI-3: pit hardening to harvest) were applied to 6-year-old Arbequina hedgerows in a semi-arid environment of Argentina over three consecutive seasons. The mean applied water reduction was 12% for DI-1 and 16% for DI-2 and DI-3, compared to Control (100% of ETc throughout the cycle). DI-3 achieved the narrowest hedgerows at harvest, where canopy height was responsive to irrigation and canopy width was affected by fruit load but not by the irrigation regime. DI-1 demonstrated similar fruit and oil yields to Control throughout the experiment, while DI-2 only had comparable yields to Control in Off-season. DI-3 had the lowest oil yields, averaging – 27% in Off and On-seasons. The fruit number was similar among treatments in all seasons, indicating that differences in final yield were related to fruit size and oil concentration. Further studies are needed to determine the optimal duration and intensity of the water deficit for DI-3.